If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+2(3x-3)=4x-9
We simplify the equation to the form, which is simple to understand
3x+2(3x-3)=4x-9
Reorder the terms in parentheses
3x+(+6x-6)=4x-9
Remove unnecessary parentheses
+3x+6x-6=+4x-9
We move all terms containing x to the left and all other terms to the right.
+3x+6x-4x=-9+6
We simplify left and right side of the equation.
+5x=-3
We divide both sides of the equation by 5 to get x.
x=-0.6
| -3(n-4)(1+5n)=n-3+5n | | 4.8x-9.1=10.1 | | 77=n+33 | | -2(-2)-9= | | 23x+20-21=19x+18-x | | Y=5(3/4x-1/5) | | 6x-65=55-4x | | 24+8=-24-6 | | -(-1)+5=6 | | 10z-5+7z-10+8z=2z-6+4z+8 | | 12=k(15) | | 3x+2+3= | | 16x-13+4=8x+10 | | 15(t-4)+6t=7(3t+3)-9 | | X=98/125 | | 3+15x-1=16x+22 | | X-1/2=2, | | 0000000000000000000000000000000000000000000000000000000000000.00000000000000000000000000000000=j | | 13.125+20+22.75+22.125+20.25+18.375+17.125+16.75+16.75+12.25=a | | 144x^2+225y^2=400 | | y^2-16y-198=0 | | 4.0=u | | 2x=6x+4x | | -16x-17=-97 | | 20=-7w+5(w+2) | | -4x+20+3=13+1 | | 17+3+(-9)= | | 4x+14=36 | | 3s+8=6 | | 3x+14-2=12x+7 | | -16x-17=97 | | x^2+10=-11 |